(untitled) (Aura: Journal for the Study of New Religions, 2023)
Spiritual awakening is becoming a common phenomenon in alternative spiritual communities and is no longer exclusive to a small elite of religious saints and disciples. There is limited research on spiritual experiences outside religious contexts in the Nordic countries. While relevant theological research exists on religious experiences in Christian contexts, much of the research on alternative spirituality is based on outsider perspectives that miss out on the deeper psychological phenomena experienced by “spiritual, but not religious” individuals. This article is based on three qualitative interviews with individuals in contemporary spiritual communities in Norway who have experienced spontaneous spiritual awakenings and speak openly about this. Focus is on the experience of altered states of consciousness, intense feelings of love, and physical energies in the body, which lead to permanent psychological transformation. Starting with a review of relevant Norwegian and Swedish research in the field, we apply a theoretical approach drawn from humanistic and transpersonal psychology to make sense of our interviewees’ experiences, and then discuss how these cases of embodied spiritual transformation differ from religious conversion and are better understood in terms of psychological concepts of trauma healing, self-actualization and human potential.